The relevance of grid expansion under zonal markets - Joachim Bertsch; Tom Brown; Simeon Hagspiel; Lisa Just (Institute of Energy Economics at the University of Cologne (EWI), 2015)
The European electricity market design is based on zonal markets with uniform prices. Locational price signals within these zones - necessary to ensure long-term efficiency - are not provided. Specifically, if intra-zonal congestion occurs due to missing grid expansion, the market design is revealed as inherently incomplete. This might lead to severe, unwanted distortions of the electricity market, both in the short- and in the long-term.In this paper, we study these distortions with a specific focus on the impact of restricted grid expansion under zonal markets. For this,we use a long term fundamental dispatch and investment model of the European electricity system and gradually restrict the allowed expansion of the transmission grid per decade. We find that the combination of an incomplete market design and restricted grid expansion leads to a misallocation of generation capacities and the inability to transport electricity to where it is needed. Consequences are severe and lead to load curtail ment of up to 2-3%.Moreover, missing grid expansion makes it difficult and costly to reach envisaged energy targets in the power sector. Hence, we argue that in the likely event of restricted grid expansion, either administrative measures or - presumably more efficient - an adaptation of the current market design to include locational signals will become necessary.
Keywords: D47; C61; C63; Q40; 330; Electricity Market; Grid Expansion; Incomplete Market Design; Misallocation; Load Curtailment